2015
DOI: 10.1108/jes-08-2013-0122
|View full text |Cite
|
Sign up to set email alerts
|

Industry level J-curve in Turkey

Abstract: Purpose – The purpose of this paper is to examine the J-Curve effect in Turkey at the industry level. Design/methodology/approach – In order to find the long-run and short-run effects, 58 industries (by Standard International Trade Classification Rev.3) have been identified by using monthly data that covers the periods from January 1990 to December 2012. Present study employs bounds testing procedure, developed by Pesaran and Shin (1999)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(40 citation statements)
references
References 32 publications
1
34
0
5
Order By: Relevance
“…Table 1 reports the results. For more on the application of these methods see (Delatte and Lopez-Villavicencio 2012;Bahmani-Oskooee and Fariditavana 2015;Bahmani-Oskooee and Sujata 2015;Durmaz 2015;Baghestani and Kherfi 2015;Pal and Mitra 2016;Al-Shayeb and Hatemi-J 2016;Lima et al 2016;Nusair 2017;Aftab et al 2017;Gregoriou 2017 From the short-run estimates of the linear models reported in Panel A, we gather that policy uncertainty measure has a significant effect on oil prices in the cases of Canada, Europe, Japan, Russia, South Korea, and the U.S. In all the cases, the effects are adverse, implying that increased uncertainty in any of these countries has adverse effects on oil prices.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 reports the results. For more on the application of these methods see (Delatte and Lopez-Villavicencio 2012;Bahmani-Oskooee and Fariditavana 2015;Bahmani-Oskooee and Sujata 2015;Durmaz 2015;Baghestani and Kherfi 2015;Pal and Mitra 2016;Al-Shayeb and Hatemi-J 2016;Lima et al 2016;Nusair 2017;Aftab et al 2017;Gregoriou 2017 From the short-run estimates of the linear models reported in Panel A, we gather that policy uncertainty measure has a significant effect on oil prices in the cases of Canada, Europe, Japan, Russia, South Korea, and the U.S. In all the cases, the effects are adverse, implying that increased uncertainty in any of these countries has adverse effects on oil prices.…”
Section: Resultsmentioning
confidence: 99%
“…Rose ve Yellen (1989), Rose (1990), Wilson ve Tat (2001), Akbostanci (2004), Narayan ve Narayan (2004), Yamak ve Korkmaz (2005), Karagöz ve Doğan (2005) , Peker (2008), Halicioglu (2008), Yazici ve Ahmad Klasra (2010) Jeğrisini destekleyecek bir kanıt bulamamıştır. Demirden ve Pastine (1995), Kale (2001), Vergil ve Erdoğan (2009), Jamilov (2013, Durmaz (2015) Karamelikli (2016) ise, J-eğrisinin bazı ülkeler için geçerli olmasına rağmen diğer ülkeler için geçerli olmadığını göstermişlerdir.…”
Section: Introductionunclassified
“… For some other application of these models see Apergis and Miller (), Delatte and Lopez‐Villavicencio (), Verheyen (), Gogas and Pragidis (), Durmaz (), Baghestani and Kherfi (), Al‐Shayeb and Hatemi‐J (), Lima et al . (), Nusair (), Aftab et al .…”
mentioning
confidence: 99%